2014
DOI: 10.1186/1471-2407-14-652
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic importance of jaundice in surgical resection with curative intent for gallbladder cancer

Abstract: BackgroundPreoperative jaundice is frequent in gallbladder cancer (GBC) and indicates advanced disease. Resection is rarely recommended to treat advanced GBC. An aggressive surgical approach for advanced GBC remains lacking because of the association of this disease with serious postoperative complications and poor prognosis. This study aims to re-assess the prognostic value of jaundice for the morbidity, mortality, and survival of GBC patients who underwent surgical resection with curative intent.MethodsGBC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…More recently, in 2014, investigators from Shanghai, China reported a 5-year survival of 6% in 47 patients with GBC and jaundice undergoing surgical resection. 13 Taken together, the results of these 5 previous studies appear to be in agreement with our study, where the actuarial 5-year survival for jaundiced GBC patients undergoing resection was noted to be 9%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More recently, in 2014, investigators from Shanghai, China reported a 5-year survival of 6% in 47 patients with GBC and jaundice undergoing surgical resection. 13 Taken together, the results of these 5 previous studies appear to be in agreement with our study, where the actuarial 5-year survival for jaundiced GBC patients undergoing resection was noted to be 9%.…”
Section: Discussionsupporting
confidence: 93%
“…Approximately a quarter to a third of patients with GBC present with obstructive jaundice, 3, 6, 13 and resectability rates among jaundiced patients has been reported to be anywhere between 7% and 49%. 14, 3, 15, 6 While surgical resection is the single potentially curative option in this setting, there is no firm consensus on the appropriateness of surgery for jaundiced patients with GBC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus preoperative jaundice should be considered a relative contraindication to radical resection for GBC [33]. However, recent reports have demonstrated declared that although preoperative jaundice indicates poor prognosis and high postoperative morbidity, it does not preclude radical resection, especially in highly selected patients (N0) [34,35], and aggressive surgery might improve long-term survival in advanced GBC patients with obstructive jaundice [36]. In this study, patients with obstructive jaundice who underwent curative resection had overall survival that were similar to those in patients without obstructive jaundice, and jaundice at diagnosis showed no prognostic impact once R0 was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the treatment of GBC in recent years, the majority of patients eventually develop local recurrent or distant metastatic disease, which is associated with a poor prognosis and an overall 5-year survival rate of <10% (4)(5)(6)(7). Early diagnosis, which is crucial for long-term survival of GBC patients, unfortunately occurs only accidentally in patients undergoing cholecystectomy for gallstones or cholecystitis, while the majority of the patients present with advanced metastatic disease due to the absence of specific symptoms and efficient biomarkers (8)(9)(10)(11)(12). Additionally, coadjuvant therapy consisting of chemotherapy and̸or radiotherapy has not yet proved beneficial in terms of patient survival (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%